Volatility Spillover between Stock Returns and Oil Prices in ASEAN: A Post-Pandemic Reassessment Using EGARCH - Khalid, Teuku Abdul; Alexandri, Mohammad Benny; Sumadinata, Widya Setiabudi; Yunus, Mukhlis (International Journal of Energy Economics and Policy, 2025)
This paper re-examines the volatility spillover effects between oil prices and stock market returns in ASEAN countries in the post-COVID-19 context. Utilizing daily data from March 2021 to December 2023, the study employs the EGARCH (1,1) model to measure asymmetric volatility transmission across six ASEAN markets—Indonesia, Malaysia, Singapore, Thailand, Vietnam, and the Philippines. The findings indicate significant volatility spillovers, albeit with varying degrees of magnitude and direction compared to the pandemic period. Notably, oil price shocks continue to influence emerging ASEAN markets, reflecting heightened integration with global commodity markets. The results have practical implications for investors and policymakers in managing risk and structuring portfolios during economic normalization.